1988
DOI: 10.1677/joe.0.119r005
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Bioactive Inhibin by the Ovary of the Booroola Merino Ewe With or Without a Copy of the Fecundity (F) Gene.

Abstract: The secretion rates of bioactive inhibin, oestradiol and progesterone were measured during the mid-luteal phase and at various times during the follicular phase of the cycle by a sensitive bioassay using sheep pituitary cells in culture in 12 Booroola ewes with and without copies of the Fecundity (F) gene in which the left ovary had been auto-transplanted to the neck. Inhibin secretion was high during the luteal phase and fell in the early follicular phase in all genotypes (P less than 0.01). In Booroola ewes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The present results are, in part, at variance with those of Tsonis et al (1988) who, although reporting no gene differences in inhibin secretion during the luteal phase, noted a significant differ¬ ence at 48 h but not at 24 or 36 h after cloprostenol injection with a higher secretion rate in + /BB animals than in ++ animals. In our study no gene-specific differences in plasma inhibin were noted at any time during the follicular or luteal phase.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The present results are, in part, at variance with those of Tsonis et al (1988) who, although reporting no gene differences in inhibin secretion during the luteal phase, noted a significant differ¬ ence at 48 h but not at 24 or 36 h after cloprostenol injection with a higher secretion rate in + /BB animals than in ++ animals. In our study no gene-specific differences in plasma inhibin were noted at any time during the follicular or luteal phase.…”
Section: Discussionsupporting
confidence: 60%
“…In our study no gene-specific differences in plasma inhibin were noted at any time during the follicular or luteal phase. In part, the discrepancy may be explained by the fact that, in the study by Tsonis et al (1988), only four B+ or BB animals and six ++ animals were examined and that these animals experienced their pre-ovulatory LH surges at markedly different times after cloprostenol injection (i.e. 48 h to > 72 h).…”
Section: Discussionmentioning
confidence: 99%
“…(Lincoln et al, 1990). Preliminary data suggest that Booroola Merino ewes ( + F or FF) carrying the high fecundity gene secrete the same amount of oestradiol and inhibin as those without the gene ( ++ ) (Tsonis et al, 1988c). The preovulatory follicles of the + F ewes are smaller and contain fewer granulosa cells than in ++ controls (Baird et al, 1982).…”
Section: Second Fsh Peakmentioning
confidence: 99%
“…Recently Wang et al (16) concluded that the reduction of rat pituitary responsiveness to G n R H induced by inhibin might be partly related to a decrease in the number of GnRH receptors. Gene-specific differences in bioactive inhibin have been noted between FF/F + ewes and + + ewes at 36 to 48 h after prostaglandin treatment, but not at Day 14 of the oestrous cycle (14). It remains to be determined whether gene-specific differences exist in inhibin secretion at other times of the oestrous cycle in Booroola ewes.…”
Section: Discussionmentioning
confidence: 99%